Effectiveness of a Home-Based Postal and Telephone Physical Activity and Nutrition Pilot Program for Seniors - Andy H. Lee; Jonine Jancey; Peter Howat; Linda Burke; Deborah A. Kerr; Trevor Shilton (Journal of Obesity)
Objective. To evaluate the effectiveness of a 12-week home-based postal and telephone physical activity and nutrition pilot program for seniors. Methods. The program was delivered by mailed material and telephone calls. The main intervention consisted of a booklet tailored for seniors containing information on dietary guidelines, recommended physical activity levels, and goal setting. Dietary and walking activity outcomes were collected via a self-administered postal questionnaire pre- and postintervention and analysed using linear mixed regressions. Of the 270 seniors recruited, half were randomly selected for the program while others served as the control group. Results. The program elicited favourable responses. Postintervention walking for exercise/recreation showed an average gain of 27 minutes per week for the participants in contrast to an average drop of 5 minutes for the controls (P<.01). Little change was evident in errand walking for both groups. The intervention group (n=114) demonstrated a significant increase in fibre intake (P<.01) but no reduction in fat intake (P>.05) compared to controls (n=134). Conclusions. The participants became more aware of their health and wellbeing after the pilot program, which was successful in increasing time spent walking for recreation and improving fibre intake.